Створення та корекція зображення за допомогою текстових підказок у діалозі - Левицький, К. Ю.; Терзіян, В. Я. (ХНУРЕ, 2025)
Generative AI models for image creation use text prompts by encoding them into numerical representations with transformers and applying diffusion models to refine noisy images. The process involves multiple convolution operations to gradually enhance image quality. These models understand not only keywords but also contextual relationships, allowing for complex scene generation. To enhance generated images, high-resolution upscaling methods reduce blurriness and ensure stylistic consistency. Further research is needed to improve precision, reduce variability, and optimize user control over AI-generated visuals.
Keywords: корекція зображення; текстові підказки